2014
DOI: 10.1080/00103624.2014.941856
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Ion Exchange as a Sign of Soil Quality

Abstract: A hypothesis is tested that allows study of not only the quantity but also the quality of ion exchange in soils, composts, peats, and its mixtures, which is common in natural and synthetic ion exchangers, on the basis of the ion-exchange process and its selectivity. For practical application of ion exchange in the soil not only the quantity of base cations and hydroxon ions bound by the solid soil phase is significant but also their readiness to ion exchange or ion exchange elasticity. Selectivity of ion excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…IEC values ranged from 52 mmol + 100 g -1 in layers IV and III, to 60 mmol + 100 g -1 in the older layers (II and I), but with no statistical differences. The values observed were greater than in a previous study utilising peat (28.8 mmol + 100 g -1 ), and garden compost (35.2 mmol + 100 g -1 ), but lower than a synthetic cation exchanger (90.5 mmol + 100 g -1 ) as determined by Váchalová et al (2014). Mature vermicompost should have significant sorption and ion-exchange properties, and release nutrients gradually to optimise the composition of the soil solution.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…IEC values ranged from 52 mmol + 100 g -1 in layers IV and III, to 60 mmol + 100 g -1 in the older layers (II and I), but with no statistical differences. The values observed were greater than in a previous study utilising peat (28.8 mmol + 100 g -1 ), and garden compost (35.2 mmol + 100 g -1 ), but lower than a synthetic cation exchanger (90.5 mmol + 100 g -1 ) as determined by Váchalová et al (2014). Mature vermicompost should have significant sorption and ion-exchange properties, and release nutrients gradually to optimise the composition of the soil solution.…”
Section: Resultscontrasting
confidence: 63%
“…The element concentrations were determined using inductively coupled plasma optical emission spectrometry (ICP-OES, VARIAN VistaPro, Varian, Australia) with axial plasma configuration. The ion-exchange capacity (IEC) was determined conductometrically as described by Váchalová et al (2014). Samples for the phospholipid fatty acid (PLFA) analysis were extracted in triplicate using a mixture of chloroform, methanol, and phosphate buffer (1:2:0.8; v/v/v) according to Bligh and Dyer (1959).…”
Section: Methodsmentioning
confidence: 99%
“…The active pH value and the EC were conducted on samples mixed with demineralised water (1:5 w/v wet basis) using a WTW pH 340 i and WTW cond 730, respectively, according to BSI EN 15933 (2012). The ion-exchange capacity (IEC) was evaluated conductometrically according to Váchalová et al (2014). For the determination of the total carbon (C tot ) and nitrogen (N tot ), a CHNS Vario MACRO cube (Elementar Analysensysteme GmbH, Germany) analyser was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The high change in C LSOM would be attributed to the fact that this fraction of soil organic matter is more active, mineral-free, and made up of highly oxidizable, partially decomposed plant and animal residues, with a high turnover [48,60]. The more the soil is disturbed, the more the labile fraction oxidizes [5,103]. Results of this experiment showed that although the TOC in the soil was affected by management practices, C LSOM was the most sensitive and was affected in the short term, as found in other studies [45,54].…”
Section: Carbon Pool (Toc C Lsom )mentioning
confidence: 99%